Bridging the Bays, Both Ways: A Janus Butterfly‐Shaped Intense NIR‐Emitting Terrylene Diimide. (9th June 2022) - Singh Mehra, Kundan; Jha, Shivangee; Bhandary, Subhrajyoti; Mandal, Dipendranath; Mishra, Ruchika; Sankar, Jeyaraman
Abstract: Molecules with intense near‐IR (NIR) emission are beneficial for modern applications such as night vision, bio‐imaging etc. However, elaborate synthetic manipulations make them demanding to accomplish. Herein, we present a simple yet exciting strategy to obtain novel Janus butterfly‐shaped terrylene diimide derivatives with carbazole wings having absorption and intense emission in the NIR. Especially, unsymmetrically substituted terrylene diimides (TDIs) have been observed to have impressive emission quantum yields (up to 93 %), highest for this class of compounds. Minimal structural distortion as evidenced from structural characterization has been shown to correlate with these observations. Also, a novel two‐tiered TDI‐carbazole having an intense emission at 897 nm is also reported. Our strategy demonstrates that efficient near‐IR luminophores can be achieved via precise functionalization. Abstract : Flying colours: Molecules with intense NIR emission are challenging to achieve. A strategy towards the development of new strongly NIR‐emissive rylene diimides (RDIs) in quantum yields up to 90 %, having extended conjugation with restricted dynamics is reported. One of the molecules reported here, with conjugated carbazole wings, resembles a Janus butterfly.